Identifikasi Interaksi Kimia Fisika Pada Kombinasi Antibiotika Amoksisilina Trihidrat - Kalium Klavulanat Dengan Kalorimeter Larutan Dan Rekristalisasi - Nugrahani, Ilma; Asyarie, Sukmadjaja; N.S, Sundani; Ibrahim, Slamet (UI Scholars Hub, 2007)
Physico-chemical interaction of amoxicillin trihydrate - potassium clavulanate has been investigated. The method used in this experiment was solution calorimeter analysis that was collaborated by the re-crystallization observation. Amoxicillin-clavulanate were mixed on the variety ratios (0:10; 9:1; ...; 1:9; 0:10) and analyzed by solution calorimeter in the HCl 0,1 N and phosphate buffer pH 6,8 solution as the gastrointestinal liquids. After that, the re-crystallizations of amoxicillin-clavulanate on the variety ratios were analyzed by polarization microscope and digital camera. The results of observation showed that amoxicillin-clavulanate have the physical-chemical interactions in the ratios 3:7; 5:5; 7:3 respectively in both of pH models of gastrointestinal liquids.